Aspectos lógicos de la intuición : aproximación al análisis de una decisión económica en un contexto de globalización (2018)
ABSTRACT: The objective of this article is to show the usefulness of the analysis of a decision that takes into account the logical aspects of intuition. To do that, at a first moment, we define what we understand by decision and intuition, and what we identify as its logical aspects. Then, we present a case of decision making of a vice president of an investment company in stock market, placing some important aspects in relation to globalization, the central theme of these days. Next, we highlight the logical-intuitive elements that appear in the decision-making process of the analyzed case. Finally, we argue what role intuition plays in this case of economic decision making in a context of globalization and what implications this proposal of analysis has on the existential decisions that, in the end, can end up being each of the decisions we make.